2018
DOI: 10.1186/s12883-018-1140-2
|View full text |Cite
|
Sign up to set email alerts
|

Altered development of dopaminergic neurons differentiated from stem cells from human exfoliated deciduous teeth of a patient with Down syndrome

Abstract: BackgroundDown syndrome (DS) is a common developmental disorder resulting from the presence of an additional copy of chromosome 21. Abnormalities in dopamine signaling are suggested to be involved in cognitive dysfunction, one of the symptoms of DS, but the pathophysiological mechanism has not been fully elucidated at the cellular level. Stem cells from human exfoliated deciduous teeth (SHED) can be prepared from the dental pulp of primary teeth. Importantly, SHED can be collected noninvasively, have multipote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 35 publications
3
11
0
Order By: Relevance
“…In this study, SHEDs were obtained from children with DS and were differentiated into DNs in vitro to elucidate the neuropathology of DS. DS‐DNs showed no apparent defects in their differentiation; however, they exhibited impaired neurite development and altered expression of DAT1 and VMAT2 , as previously reported in the analysis of a single case of DS 29 . We also found that DAT1 upregulation via DLK1 downregulation may be implicated in dopamine accumulation and ROS elevation in DS‐DNs.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…In this study, SHEDs were obtained from children with DS and were differentiated into DNs in vitro to elucidate the neuropathology of DS. DS‐DNs showed no apparent defects in their differentiation; however, they exhibited impaired neurite development and altered expression of DAT1 and VMAT2 , as previously reported in the analysis of a single case of DS 29 . We also found that DAT1 upregulation via DLK1 downregulation may be implicated in dopamine accumulation and ROS elevation in DS‐DNs.…”
Section: Discussionsupporting
confidence: 84%
“…In the second step, DMEM was replaced by neurobasal medium (Thermo Fisher Scientific) supplemented with 2% B27 supplement (Thermo Fisher Scientific), 1 mM dibutyryladenosine 3,5‐cyclic monophosphate (Nacalai Tesque), 0.5 mM 3‐isobutyl‐1‐methyl‐xanthine (Wako Pure Chemical Industries), and 200 μM ascorbic acid (Nacalai Tesque) (second medium), and cells were incubated for 5 days at 37°C in an incubator with 5% CO 2 . As previously reported, DNs were not fully matured at this stage to allow the strict discrimination between dendrites and axons 29 …”
Section: Methodsmentioning
confidence: 79%
See 2 more Smart Citations
“…They may also experience emotional and behavioral challenges [20][21][22][23], which greatly impact the quality of life of these patients and of the people who care for them. As dopamine (DA) is an important neurotransmitter for cognitive function regulation, it has been pointed out that DA signaling system disturbance causes the cognitive impairments observed in DS [24][25][26][27][28]. DA systems are subject to an accelerator/brake control of their activity [29], which is pivotal for finely shaping DA responses [29,30].…”
Section: Introductionmentioning
confidence: 99%